Haptic heritage and the paradox of provenance within Singapore's cottage food businesses. (15th March 2022) - Woods, Orlando; Donaldson, John
ABSTRACT: This paper offers a "more-than-representational" understanding of how heritage value is reproduced by cottage food businesses in Singapore. It advances the notion of haptic heritage to highlight the importance of touch and feel in inculcating food with a sense of heritage value. Haptic heritage is reproduced through the physical handling of ingredients in ways that contribute to more "authentic" products. However, it also foregrounds food production processes that are more tactile, time-consuming and thus unscalable than their automated counterparts. Accordingly, the reproduction of haptic heritage is becoming increasingly unviable in Singapore's competitive economic landscape. These ideas are explored through a supply-side analysis of interviews conducted with owners of cottage food businesses in Singapore. We highlight the importance of provenance in passing on haptic knowledges over multiple generations of business owners, the affective value and inefficiency of haptic knowledges, and the present-day politics of provenance. To conclude, we call for research to continue to explore the ways in which sensory forms of heritage are understood and (under)valued in the contemporary world.